Development and validation of a qPCR assay for the detection of residual host cell DNA in rabies vaccines produced in Vero cells - Zhao, Danhua; Zong, Weiying; Wu, Wanxin; Li, Yuhua; Wu, Zongsong; Yang, Zhixing; Cao, Shouchun (Frontiers in Bioengineering and Biotechnology, 2025)
Residual host cell DNA in biological products, including rabies vaccines, poses potential health risks such as tumorigenesis and infectivity. Regulatory authorities have set limits for residual DNA levels to ensure product safety. Among various detection methods for residual DNA, quantitative PCR (qPCR) is recognized for its high sensitivity and efficiency. This study developed and validated a qPCR assay for detecting residual Vero DNA in rabies vaccines produced in Vero cells. The assay targeted two highly repetitive Vero genomic DNA sequences: the “172bp” sequence and the Alu repetitive sequence. The method was optimized and validated for linearity, range, quantitation limit, detection limit and specificity, etc. The qPCR assay for the “172bp” sequence exhibited excellent linearity, with a quantification limit of 0.03pg/reaction and a detection limit of 0.003pg/reaction. The relative standard deviation (RSD) across samples ranged from 12.4% to 18.3%, and the recovery rate was between 87.7% and 98.5%. No cross-reactivity was observed with common bacterial and cell strains, indicating a high specificity of the assay. These findings suggest that the qPCR method is a reliable approach for quantifying residual Vero DNA in pharmaceuticals and for regulatory compliance monitoring. The assay method has been adopted by local vaccine manufacturers, and has been included in the Chinese Pharmacopoeia, thus will help to enhance vaccine quality and safety.